The extension of the infant gross motor screening test to include infants from birth to five months in infants with HIV - Otten, Kirsty Mae (My University, 2018)
The aim of this study was to extend the age range of the Infant Gross Motor Screening Test (IGMST) to make it appropriate for use in infants infected with HIV from birth to five months. Previously completed Bayley Scales on Infant and Toddler Development (3rd Version) (BSID III) assessments, from two 2013 physiotherapy masters studies completed through the University of the Witwatersrand, were used to compile neurodevelopmental scores achieved by infants infected with HIV. These scores were used to select developmentally appropriate items for inclusion in the new section of the IGMST. These items were statistically tested against the original BSID III scores using the Pearson correlation coefficient. Following statistical testing, content validity of the new section of the IGMST was established with an expert panel using a modified nominal group technique (NGT). The new section of the IGMST included two age bands; one to three months and four to five months. Each age band consisted of five items. Age band one to three months had a Pearson correlation coefficient of r =0.68 (p = 0.003) and 84% of the infants performed the same on both tests. Age band four to five achieved a Pearson correlation coefficient r = 0.71 (p = 0.0009) and 83% of infants performed the same on both tests. When presented to the expert panel using a modified NGT, all items and questions raised were accepted by 100% after appropriate adjustments were made. In conclusion, the new section of the IGMST has been developed for infants from one to five months and the content validity has been established during the course of this study. The new section must still undergo further validity and reliability testing before it can be used clinically.
A research report submitted to the Faculty of Health Science, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements of the degree of Master of Science in Physiotherapy Johannesburg, 2018.
Keywords: Infant Gross Motor Screening Test (IGMST); HIV; Infant